ELECTRONIC SYSTEM FOR MONITORING DRIVER’S HEALTH IN THE VEHICLE - MUKHIN, ANTON; PETRENKO, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
It is proposed to integrate an additional system of automated monitoring of the driver’s health while driving into the assistance unit of a modern car. The main purpose of such a system is to take care of critical health indicators such as temperature, heart pressure, blood oxygen level in percentage ratio, electrocardiogram indicators, photoplethysmography and sound examination of the lungs, and heart-stethoscopy. Electronic circuits for implementing the control of this system and its integration into the main electronic unit of the car using a special protocol based on the universal serial interface are proposed.